EXAMINING THE LEGAL STANDING OF DIGITAL SIGNATURES UNDER CIVIL AND ITE LAWS - Desak Ayu Intan Diah Iswari; Dewa Gede Rudy (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
This research aims to investigate the validity of digital signatures and their evidential value. This study adopts a normative juridical approach, utilizing a statutory method. The findings of this study reveal that: (1) Digital signatures have evidential strength as they are recognized by Article 5 of the ITE Law and are legally binding in civil cases in accordance with the relevant procedural laws of Indonesia. (2) In terms of legality under Indonesian positive law, digital signatures contained in electronic documents are considered valid in civil law, in accordance with the provisions of Article 1320 of the Civil Code and the enactment of Law Number 19 of 2016 Amendment to Law Number 11 of 2008, as well as Government Regulation No.71 of 2019, which deals with the Implementation of Electronic Systems and Transactions.